Needle Bending in a VR-Puncture Training System Using a 6DOF Haptic Device - Matthias Färber; Thorsten Dahmke; Christian-Arved Bohn; Heinz Handels (MMVR17, 2009)
The use of virtual reality techniques opens up new perspectives to support and improve the puncture training in medical education. In this work a 3D VR-Simulator for the training of lumbar and ascites punctures has been extended to support the bending of the puncture needle. For this purpose the needle is designed as an angular spring model. The forces that restrict the user from bending the needle are calculated using a multiproxy technique and given to the user via a 6DOF haptic device (Sensable Phantom Premium 1.5). Proxy based haptic volume rendering is used to calculate the proxy movement. This way it is possible to integrate original CT-patient data into the rendering process and generate forces from structures that have not been segmented. The bending technique has been integrated in a VR-training system for puncture interventions and shows good results concerning update rate and user acceptance.
Keywords: Biopsy, Needle; Computer Simulation; Education, Medical; Feedback; Humans; Imaging, Three-Dimensional; Touch; User-Computer Interface